PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS X MIA 3 MAN 3 PEKANBARU - Dewi, Widya Shintya; Heleni, Susda; Jalinus, Jalinus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research is classroom action research which aims to improve the learning process and the result of learning mathematics by applying problem based learning (PBL) model. The subject of this research is student of class X MIA 3 MAN 3 Pekanbaru in academic years 2018/2019, which amounted to 29 students. Instruments on this reserach constisted of syllabus, lesson plans and worksheets, and instruments of data collection which is observation sheets and the test result sheets. The function of observation sheet is to obtain data from the learning process, while the function of results sheet of the mathematics learning tests is to obtain the results of the study. The data obtained are then analyzed by the technique of analyzing the data of teacher and student activities as well as data analysis of student mathematics learning outcomes. The descriptive of observation sheets through the stage of data reduction, data exposure and inference and students’ mathematic tests showed an improvement of learning process prior to the action on the first and second cycles and improve the students’ achievement of learning mathematic. On the knowledge competence, from the basic score of 3 students or 10,34% increased to 15 students or 34,48% in the first cycle and increased to 14 students or 48,28% in Cycle II. On the skills competence, the number of students who reach the minimum criteria of mastery learning from Cycle I of 9 students or 31% improve to 15 students or 51,7% in cycle II. The results of this analysis indicate that the implementation of the PBL model can improve the learning achievement students of class X MIA 3 MAN 3 Pekanbaru academic year 2018/2019.Key Words: Students’ Mathematic Achievement, Problem Based Learning, Class Action Research